AP‐1A Controls Secretory Granule Biogenesis and Trafficking of Membrane Secretory Granule Proteins. (15th August 2014) - Bonnemaison, Mathilde; Bäck, Nils; Lin, Yimo; Bonifacino, Juan S.; Mains, Richard; Eipper, Betty
Abstract The adaptor protein 1A complex (AP‐1A) transports cargo between the trans‐Golgi network (TGN) and endosomes. In professional secretory cells, AP‐1A also retrieves material from immature secretory granules (SGs). The role of AP‐1A in SG biogenesis was explored using AtT‐20 corticotrope tumor cells expressing reduced levels of the AP‐1A μ1A subunit. A twofold reduction in μ1A resulted in a decrease in TGN cisternae and immature SGs and the appearance of regulated secretory pathway components in non‐condensing SGs. Although basal secretion of endogenous SG proteins was unaffected, secretagogue‐stimulated release was halved. The reduced μ1A levels interfered with the normal trafficking of carboxypeptidase D (CPD) and peptidylglycine α‐amidating monooxygenase‐1 (PAM‐1), integral membrane enzymes that enter immature SGs. The non‐condensing SGs contained POMC products and PAM‐1, but not CPD. Based on metabolic labeling and secretion experiments, the cleavage of newly synthesized PAM‐1 into PHM was unaltered, but PHM basal secretion was increased in sh‐μ1A PAM‐1 cells. Despite lacking a canonical AP‐1A binding motif, yeast two‐hybrid studies demonstrated an interaction between the PAM‐1 cytosolic domain and AP‐1A. Coimmunoprecipitation experiments with PAM‐1 mutants revealed an influence of the luminal domains of PAM‐1 on this interaction. Thus, AP‐1A is crucial for normal SG biogenesis, function and composition. <inline-graphic xlink:href="ark:/27927/pgh1c9m0wsr" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />